Sofia Petrovna - Lydia Chukhovskaya ; translated by Aline Worth, revised and amended by Eliza Kellogg Klose. (Northwestern University Press, 1988)
Translation of: Opustelyi dom. First English language ed. published in 1967 as: The deserted house.